Athletes and sleep issues: new insights into translating laboratory findings in a real-world setting - Botonis, P. G.; Grammenou, M.; Toubekis, A. G. (Sports Health: A Multidisciplinary Approach, 2025)
To date, the influence of sleep loss on recovery, health, and performance has been examined mostly in well-controlled laboratory conditions, where physically active or recreational athletes participate in experimental conditions requiring them to undergo sleep deprivation, early sleep restriction (i.e., to remain awake until a predetermined hour in the night and to sleep thereafter), or late sleep restriction (i.e., going to bed at a regular time, waking-up earlier than usual, and staying awake thereafter). Despite their importance, such laboratory findings may not replicate what happens in an athletes` life and, thus, transferring such findings to a real-world sport setting is questionable. In the present editorial, we aim to identify gaps between laboratory findings and the real-life stressors making athletes vulnerable to sleep loss. Further, we shed light on methodological constraints hindering the transfer of existing evidence in a real-world athletic setting, stimulating further research on this growing and promising area of research.